Analisis metafora dalam novel Elachia Payanam / Manokaran Rengasamy - Manokaran , Rengasamy (2019)
Metaphors are one of the important elements in literary work. The elements which have been used as metaphors in a piece of writing can illustrate the thinking, culture, beliefs, lifestyle and humans’ feelings. Therefore, a study aimed at analyzing the types of metaphors and different interpretation of metaphorical meanings between the novelist and respondents had been carried out. In this study which had used the descriptive qualitative approach, the researcher made a total of 30 metaphors as the main sample of the study to analyze the elements that are used as metaphors in the novel. The researcher used Lakoff and Johnson’s (1980) conceptual theory of metaphors to analyze the Elachia Payanam novel in order to identify the types of metaphors existed in the novel. In addition, differences in the interpretations of the metaphors among the Tamil teachers had also been studied. The findings of the study showed that the novelist had used structural metaphors and ontologies to illustrate the metaphors. Some elements of flora and fauna were used as domain resources (SD) to show metaphors. The use of these elements demonstrated the lifestyle, way of thinking and beliefs of the Tamil people living in the estates. A total of 60 percent of the interpretations given by the teacher were accurate. This is due to the fact that the use of several Tamil terms by the novelist was different with the northern states of Peninsular Malaysia. Additionally, it was also identified that the understanding of context, thinking and culture were also the cause of different interpretation. In conclusion, the use of metaphors does bring various interpretations based on several factors.